On the Stability of Semilinear Nonautonomous Evolution Equations in Banach Spaces and Its Application to Strongly Parabolic Equations - Tran Thi Loan; Nguyen Manh Hung (Український математичний журнал, 2002)
The paper is concerned with the exponential stability of the zero solution of strongly nonautonomous parabolic equations. Conditions are found on time-dependent coefficients of a parabolic equation under which its solutions converge exponentially to 0 as t → ∞. Розглядається експоненціальна стійкість нульового розв'язку сильно неавтономних параболічних рівнянь. Знайдено умови для залежних від часу коефіцієнтів параболічного рівняння, при яких його розв'язки експоненціально збігаються до 0 при t → ∞.